External electrical cardioversion in patients with cardiac implantable electronic devices: Is it safe and is immediate device interrogation necessary?. Issue 10 (28th August 2018) - Pluymaekers, Nikki AHA; Dudink, Elton AMP; Boersma, Lucas; Erküner, Ömer; Gelissen, Marloes; van Dijk, Vincent; Wijffels, Maurits; Dinh, Trang; Vernooy, Kevin; Crijns, Harry JGM; Balt, Jippe; Luermans, Justin GLM
Abstract: Background: Atrial tachyarrhythmias are common in patients with cardiac implantable electronic devices (CIEDs). Restoration of sinus rhythm by external electrical cardioversion (eECV) is frequently used to alleviate symptoms and to ensure optimal device function. Objectives: To evaluate the safety of eECV in patients with contemporary CIEDs and to assess the need for immediate device interrogation after eECV. Methods: We conducted a retrospective observational study of 229 patients (27.9% female, age 69 ± 10 years) with a CIED (104 pacemakers, 69 implantable cardioverter defibrillators, and 56 biventricular devices) who underwent eECV between 2008 and 2016 in two centers. Data from device interrogation before eECV, immediately afterwards, and at first follow‐up (FU) after eECV were collected. CIED‐related complications and adverse events during and after eECV were recorded. Results: No significant differences between right atrial (RA) and right ventricular (RV) sensing or threshold values before eECV, immediately afterwards, or at FU were observed. A small yet significant decrease was observed in RA and RV impedance immediately after eECV (484 Ω vs 462 Ω, P < 0.001 and 536 Ω vs 514 Ω, P < 0.001, respectively). The RV impedance did not recover to the baseline value (538 Ω vs 527 Ω, P = 0.02). The impedance changes were without clinical consequences. No changes in left ventricular lead threshold or impedance values were measured. No CIED‐related complications or adverse events were documented following eECV. Conclusion: eECV in patients with contemporary CIEDs is safe. There seems to be no need for immediate device interrogation after eECV.